1972
DOI: 10.1037/h0033156
|View full text |Cite
|
Sign up to set email alerts
|

More on the Protestant Ethic.

Abstract: Protestant Ethic Scale was administered to 101 (70 females and 31 males) undergraduate students. As predicted, endorsement of the Protestant Ethic was significantly related to negative attitudes toward the poor and opposition to a guaranteed minimum annual income, as measured by A. P. MacDonald's Poverty Scale. Endorsement of the Protestant Ethic was positively related to authoritarianism and J. E. Rotter's internal locus of control (the latter for males only). A modified format and scoring procedure for M. Ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0
1

Year Published

1980
1980
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(66 citation statements)
references
References 8 publications
4
61
0
1
Order By: Relevance
“…As found in the previous studies (Miréis and Garrett, 1971;MacDonald. 1972), the PE scores were significantly, positively related to authoritarianism among both groups of Chinese students.…”
Section: Miréis and Garrettsupporting
confidence: 61%
“…As found in the previous studies (Miréis and Garrett, 1971;MacDonald. 1972), the PE scores were significantly, positively related to authoritarianism among both groups of Chinese students.…”
Section: Miréis and Garrettsupporting
confidence: 61%
“…Using the OWEI, Minton (1997) found a significant difference between employers' expectations of work ethic and the self-perceived work ethic of secondary school students. In terms of the relationships between education and work attitudes, some researchers (Goodale, 1973;Wollack et al, 1971) found positive relationships, while others (Aldag & Brief, 1975;Buchholz, 1978;MacDonald, 1972) found no relationship or negative relationships (Tang & Tzeng, 1992). Petty (1995) found significant positive differences in OWEI measured work ethic for the age group 36-55 over the other four age groups studied.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Protestant work ethic endorsement, determinants are felt to be primarily a function of personality and secondarily a reflection of culture. The personality link is based on observations that ethic endorsement covaries with other stable personality traits (e.g., higher order need strength- Wanous, 1974;locus of control-McDonald, 1972;Waters et al, 1975;authoritarianism-Greenberg, 1977;MacDonald, 1972); and demographic traits (e.g., age- race-Bhagat, 1979). Moreover, work ethic measures have been found to be important moderators between such situational factors as job characteristics and work reactions (Greenberg, 1977;Wanous, 1974).…”
Section: Determinantsmentioning
confidence: 99%